Anticipated impact of recent ethanol lock shortage and price increase on practice among pediatric intestinal rehabilitation programs across the United States. Issue 2 (25th May 2021) - Talathi, Saurabh; Mezoff, Ethan; Galloway, David; Rahhal, Riad
Abstract : Background: Ethanol lock use has been associated with significantly lower rates of central line–associated bloodstream infection (CLABSI) in children with intestinal failure. Concerns have been raised among intestinal rehabilitation program providers regarding the impact of recent changes in cost and availability of ethanol locks in the US. Methods: We conducted a survey among the members of the North American Society For Pediatric Gastroenterology, Hepatology & Nutrition Intestinal Rehabilitation Special Interest Group (NASPGHAN IR‐SIG) regarding practice changes among providers to tackle this issue and the anticipated effect on CLABSI rates. Results: The results show that the vast majority of US participants use ethanol locks in their population with intestinal failure, with most anticipating or already experiencing reduction in access to ethanol locks. Most worrisome is that more than half of participating programs expect an increase in CLABSI rates in this vulnerable patient population as a consequence of limited access to ethanol locks. Conclusion: Further multicenter prospective studies to assess the efficacy of alternative locking agents, besides ethanol, are needed in order to have readily available and affordable options for CLABSI prevention in the future.